(untitled) (Bangladesh Journal of Child Health, 2020)
Background: Incidence of dengue infection has increased worldwide and has become a significant public health concern. Clinical suspicion based on the frequency of symptoms is very important for early diagnosis. Objectives: To observe the clinical characteristics of serologically confirmed hospitalized cases of dengue fever. Material and Methods: This cross-sectional study was done among admitted children with dengue infection in Dhaka Shishu (Children) Hospital from July 2018 to October 2018. The diagnosis of dengue fever (DF), dengue hemorrhagic fever (DHF), and dengue shock syndrome (DSS) were established according to the World Health Organization (WHO) classification criteria. Cases who were NS1 antigen and IgM dengue antibody positive included in this study. Results: Among 51 serologically confirmed dengue fever patients, mean age was 6.66 ± 3.69 years. Majority of the cases (74.5%) were less than 10 years of age, 60.8% were male, 39.2% were female, and 88.23% of patients came from urban areas. Classic DF was found in 74.5% of patients, while 25.49% of patients DHF, and 11.7% DSS. Fever was the most common (72.55%) symptom followed by headache, vomiting and myalgia. Hemorrhagic manifestations found in 21.57% of cases. The most common complications were hepatic dysfunction (47.09%) followed by renal impairment, encephalopathy, multi-organ failure, and ARDS. Conclusion: The majorities of dengue cases were from urban areas, below ten years of age and classical DF. Besides fever other common symptoms were headache, vomiting and myalgia. The most common complications were hepatic dysfunction, renal impairment and encephalopathy. Bangladesh J Child Health 2020; VOL 44 (1) :30-33